Motivation and sound mass in inclusion: self-esteem in musical performance (Orfeu, 2021)
This study aims to analyze what motivates a group of visually impaired people, lay people in music, to participate in classes, rehearsals and go up on stage in front of a crowded audience. It narrates the experience of the members of the Music Transforming Lives Project - PROMUVI, in more than a decade of existence, in sharing moments of belonging, socialization and challenges, how the group is composed, the interaction of teachers and students, learning difficulties, the repertoire used and especially the motivation mechanisms that make members interested in raising their self-esteem in a spontaneous way to learn a musical instrument.
Keywords: Visual impairment; Self-steem; Performance; Musical inclusion; Motivation